A two-year outcome of intrastromal corneal ring segment implantation in keratoconus: Initial report in Thai patients - Suksri Chotikavanich (2020)
© 2019 Siriraj Medical Journal. Objective: To determine two-year outcome of intrastromal corneal ring segment (ICRS) implantation in keratoconus in Thai patients Methods: A retrospective review of medical records of the patients underwent Ferrara-type ICRS implantation (single and two segments) at Siriraj Hospital between November 2013 and December 2017 was conducted. Clinical outcomes were assessed at 1 month, 6 months, 1 year, and 2 years postoperatively. Results: Of 9 eyes in 8 patients, the mean age of the patients was 24.6 ± 7.5 years. The mean follow-up time was 32.2 ± 9.4 months. Overall, the median visual acuity was significantly improved postoperatively (p value = 0.007). At 2 years, the uncorrected visual acuity (UCVA) improved from 1.00 logMAR to 0.56 logMAR, and the corrected distance visual acuity (CDVA) improved from 0.76 logMAR to 0.10 logMAR. Correspondingly, the median spherical equivalent refraction was significantly improved postoperatively from -7.38 D to -3.13 D (p < 0.001). Moreover, the median anterior corneal topographic data significantly changed between visits (p < 0.02). The Kmax decreased from 52.65 D to 46.65 D and the Kmean decreased from 48.10 D to 45.40 D at 2 years. Postoperative adverse effects were glare and halos (3 eyes), visually insignificant small white corneal deposits around the segments (2 eyes), extrusion of a ring segment needed removal with reversible to baseline vision (1 eye). Conclusion: This initial report in Thai patients showed that the ICRS implantation in keratoconus could improve the visual, refractive, and topographic parameters with stability at 2 years. However, appropriate case selection and surgical technique should be considered.